2015
DOI: 10.1108/pmm-02-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the value and impact of library and information services. Part 1

Abstract: Purpose -The purpose of the part 1 of the series of Viewpoint papers is to examine approaches to identifying the value of library and information services, using concepts from the marketing literature, and stressing the importance of co-creating value with the service users. Design/methodology/approach -The literature review examined some of the approaches to considering value and value creation from the marketing literature. Considers approaches such as narrative based marketing, holistic value frameworks, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…These results contribute to information science, as few studies have examined ultimate outcomes of information such as health outcomes (Case & Given, ; Urquhart & Turner, ). Specifically, our work is a departure from previous studies that focus on a limited number of factors and outcomes, and usually only positive outcomes.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…These results contribute to information science, as few studies have examined ultimate outcomes of information such as health outcomes (Case & Given, ; Urquhart & Turner, ). Specifically, our work is a departure from previous studies that focus on a limited number of factors and outcomes, and usually only positive outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…Recent reviews showed few studies on information outcomes such as a change in knowledge, emotion, intention, or behavior after information is found or received; they presented exemplar studies, but did not identify types of outcomes in a comprehensive manner (Case & O'Connor, ; Urquhart & Turner, ). Since 2001, we have progressively developed levels of outcomes included in the initial framework using the “Value of information” overarching construct and the “Acquisition Cognition Application” model proposed by Saracevic and Kantor ().…”
Section: Conceptual Boundariesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is, of course, a history of value and impact research in the health sector (see Marshall et al, , on research in North America). A three‐part review of value and impact examined different perspectives on value and impact: identifying value, narrative‐based marketing, value co‐creation and perceived value typologies (Urquhart, ); impact assessment, including linking of organisational goals, information needs of users, immediate and long‐term impacts of library service use, and economic impact assessment, including return on investment (Urquhart & Turner, ); working towards an assessment culture, that incorporates frameworks (such as scorecards) and process modelling for ongoing library assessment of value, and identifying where changes are necessary (Urquhart & Tbaishat, ). …”
mentioning
confidence: 99%
“…As Germano (2011, as cited in Urquhart, 2015) states that physical visits of libraries has declined and library value deficit has become a problem. He further argues, "Libraries cannot rely on the goodwill assumption that libraries are a 'good thing'….…”
Section: Introductionmentioning
confidence: 99%